PENINGKATAN KEMAMPUAN MENULIS TEKS BIOGRAFI PADA SISWA SMA NEGERI 7 SINGKAWANG - Zefanya, Khristy Siti; Syambasril, Syambasril; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
ABSTRACT This research was backgrounded by the disclosure of class X students at SMA 7 Singkawang who have poor writing skills. The students were not able to collect information, start the beginning of the story, sequence a series of stories experienced by the figure, and have low motivations. Therefore, this research aimed to represent the planning, implementation and results from the instruction using the Picture and Picture method. This class action research was conducted in two cycles, of which each cycle comprised steps such as planning, acting, observing, and reflection. The method used was descriptive in the form of qualitative research. Data was presented qualitatively to see the level of achievement and quantitatively to identify the learning outcomes using a simple statistical method. The findings demonstrated that the selected method increased the learning results in writing biographical text. This is confirmed from (1) The instruction in cycle I and II had been organized based on the steps of the Picture and Picture method, however, one of the steps of the selected method was not incorporated in the lesson plan, and was reviewed in cycle II; (2) The implementation in cycle I was appropriately conducted; however, one step in the lesson plan was not done and thus revised in cycle II; (3) The learning outcomes improved with the average scores of the test by 69.79 in cycle I and 77.86 in cycle II. Keywords: writing biographical text, Picture and Picture Method.